ELISA-like QDB method to meet the emerging need of Her2 assessment for breast cancer patients - Yu, Guohua; Lyu, Yan; Jiang, Lei; Wang, Yunjun; Yin, Ying; Zhang, Jiandi; Yang, Maozhou; Tang, Fangrong (Frontiers in Oncology, 2023)
The inherent issues of subjectivity and inconsistency have long plagued immunohistochemistry (IHC)-based Her2 assessment, leading to repeatedly issuing of guidance by American Society of Clinical Oncology/College of American Pathologists (ASCO/CAP) for its standardization for breast cancer patients. Yet, all these efforts may prove insufficient with the advent of Trastuzumab deruxtecan (T-Dxd), the drug with the promise to expand to tumors traditionally defined as Her2 negative (Her2-). In this study, we attempted to address these issues by exploring an ELISA-like quantitative dot blot (QDB) method as an alternative to IHC. QDB method has been used to measure multiple protein biomarkers including ER, PR, Ki67 and cyclin D1 in breast cancer specimens. Using an independent cohort (cohort 2) of breast cancer Formalin Fixed Paraffin Embedded (FFPE) specimens, we validated cutoffs developed in cohort 1 (Yu et al, Scientific Reports 2020 10:10502) with overall 100% specificity (95%CI: 100-100) and 97.56% sensitivity (95%CI: 92.68-100) in cohort 2 against standard practice with the dichotomized absolutely quantitated values. Using the limit of detection (LOD) of QDB method as the putative cutoff point, tumors with no Her2 expression were identified with the number comparable to those of IHC 0. Our results support further evaluation of QDB method as an alternative to IHC to meet the emerging need of identifying tumors with low Her2 expression (Her2-low) in daily clinical practice.